2022
DOI: 10.1001/jama.2022.0799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sublingual Dexmedetomidine vs Placebo on Acute Agitation Associated With Bipolar Disorder

Abstract: IMPORTANCEAcute agitation is common in patients with bipolar disorder and requires urgent management to relieve distress and to prevent escalation to aggressive behavior.OBJECTIVE To evaluate the effect of orally absorbed, sublingual dexmedetomidine, a selective α 2A -adrenergic receptor agonist on symptoms of acute agitation in patients with bipolar disorder.DESIGN, SETTING, AND PARTICIPANTS Phase 3, randomized, double-blind, placebo-controlled trial conducted in 15 sites in the US with enrollment between Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 23 publications
2
54
0
Order By: Relevance
“…Data were taken from two similarly designed, randomized, double-blind, placebo-controlled studies that evaluated the effects of sublingual dexmedetomidine on acute agitation in patients with schizophrenia (NCT04268303) or bipolar disorder (NCT04276883) [ 19 , 20 ]. The studies were conducted between January and May 2020 at clinical sites in the United States.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were taken from two similarly designed, randomized, double-blind, placebo-controlled studies that evaluated the effects of sublingual dexmedetomidine on acute agitation in patients with schizophrenia (NCT04268303) or bipolar disorder (NCT04276883) [ 19 , 20 ]. The studies were conducted between January and May 2020 at clinical sites in the United States.…”
Section: Methodsmentioning
confidence: 99%
“…The efficacy and tolerability of 120-µg and 180-µg doses of sublingual dexmedetomidine were evaluated in two similarly designed, randomized, double-blind, placebo-controlled, phase 3 trials in the treatment of acute agitation associated with schizophrenia [ 19 ] and bipolar disorder [ 20 ]. Efficacy in both studies was measured from 10 min through 24 h post-dose using the 5-item Positive and Negative Syndrome Scale-Excited Component (PEC), a validated and commonly used research instrument for evaluating acute agitation and aggression in patients with different psychiatric pathologies [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That prediction was successfully tested in agitated patients with bipolar disorder. 1 This column also complements multiple previous columns that have discussed how novel central nervous system drugs can be developed based on an understanding of the circuitry underlying the target indications. [35][36][37][38][39] These columns also illustrate how specific forms of psychopharmacology can be tied to specific brain mechanisms and circuits, allowing for a more sophisticated way of conceptualizing and utilizing various psychopharmacological therapies.…”
Section: Neurotransmittermentioning
confidence: 91%
“…Dexmedetomidine, a lipophilic imidazole derivative, is a potent and selective agonist of α 2 -adrenergic receptors [ 13 ]. This drug has been disclosed to exert a variety of actions on the human brain such as sedation, anesthetic sparing effects, and analgesia [ 13 , 14 ]. A recent investigation has shown that dexmedetomidine could perturb on the non-equilibrium property of I h in response to triangular V ramp found in GH 3 cells [ 15 ].…”
Section: Hys (V) Behavior Residing In Hyperpolariz...mentioning
confidence: 99%